2022
DOI: 10.1038/s44161-022-00096-8
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity of the CD155 immune checkpoint suppresses anti-viral immunity in patients with coronary artery disease

Abstract: re-existing cardiovascular diseases, such as hypertension, CAD, cardiac arrhythmias and congestive heart failure, are strong risk factors for severe viral disease, complicated by high morbidity and mortality rates 1,2 . In addition, individuals with cardiovascular comorbidities fail to respond adequately against vaccines 3 . Poor anti-viral immunity in patients with CAD has been exemplified during the recent SARS-CoV-2 pandemic, where a history of CAD was associated with severe symptoms 1 . Patients with CAD g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Correspondingly, we identified by ChaC most of m 6 A regulators (e.g., writers or readers) as the COVID-19 phenotypic interactors and showed that G9a inhibition reversed the SARS-CoV-2induced m 6 A landscape (Figure 4b-4c); thus, via the METTL3-m 6 A axis, G9a regulates select SARS-CoV-2hijacked translation pathways. For example, in correlation with the observation that compromised antigen presentation by METTL3 hi CD155 hi macrophage cells diminishes antiviral T cell response against SARS-CoV-2 antigens in COVID-19 patients with coronary artery disease 90 , we found that G9a inhibition reversed the level of select m 6 A mRNAs associated with macrophage proliferation, T-cell dysfunction, and dysregulation of blood coagulation. Presently, in the absence of good clinical/pre-clinical molecules targeting m 6 A regulators (METTL3), our results demonstrate that inhibition of G9a, the upstream regulator of SARS-CoV-2 induced m 6 A epitranscriptome, represents a host mechanism-directed therapeutic approach to combat SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 84%
“…Correspondingly, we identified by ChaC most of m 6 A regulators (e.g., writers or readers) as the COVID-19 phenotypic interactors and showed that G9a inhibition reversed the SARS-CoV-2induced m 6 A landscape (Figure 4b-4c); thus, via the METTL3-m 6 A axis, G9a regulates select SARS-CoV-2hijacked translation pathways. For example, in correlation with the observation that compromised antigen presentation by METTL3 hi CD155 hi macrophage cells diminishes antiviral T cell response against SARS-CoV-2 antigens in COVID-19 patients with coronary artery disease 90 , we found that G9a inhibition reversed the level of select m 6 A mRNAs associated with macrophage proliferation, T-cell dysfunction, and dysregulation of blood coagulation. Presently, in the absence of good clinical/pre-clinical molecules targeting m 6 A regulators (METTL3), our results demonstrate that inhibition of G9a, the upstream regulator of SARS-CoV-2 induced m 6 A epitranscriptome, represents a host mechanism-directed therapeutic approach to combat SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 84%
“…The pandemic revealed a similar pattern: patients with CVD and associated risk factors, such as obesity and diabetes, had worse outcomes from COVID-19 6 . And the same seems to be true for other viruses, such as varicella zoster virus or Epstein-Barr virus 7 . Are patients with CVD more prone to severe viral disease, which in turn increases their risk of later cardiovascular events?…”
mentioning
confidence: 83%
“…In this issue of Nature Cardiovascular Research, Zhao et al aimed to address some of these knowledge gaps 7 . In an elegant co-culture model, they show that monocyte-derived macrophages from patients with coronary artery disease (CAD) -when stimulated with proteins from SARS-CoV-2 or Epstein-Barr virus -are less capable, compared to those from healthy control individuals, of presenting antigens and subsequently activating autologous T cells to help clear the virus.…”
mentioning
confidence: 99%
“…13 Moreover, individuals with CVDs exhibit increased susceptibility to severe viral infections. 14 Therefore, it is imperative to expedite all types of CVDs research. Currently, the best methods for clinically diagnosing CVDs include electrocardiogram, echocardiography, and cardiac magnetic resonance imaging (CMRI).…”
Section: Introductionmentioning
confidence: 99%
“…For example, CVDs can alter the vasculature of bone marrow in patients, leading to endothelial dysfunction, vascular leakage, and other conditions . Moreover, individuals with CVDs exhibit increased susceptibility to severe viral infections . Therefore, it is imperative to expedite all types of CVDs research.…”
Section: Introductionmentioning
confidence: 99%